Quasiconformal mappings and Neumann eigenvalues of divergent elliptic operators; Complex Variables and Elliptic Equations; Vol. 67, iss. 9 - Goldshteyn V. M. Vladimir Mikhaylovich (2022, 2022)
Title screen